2009
DOI: 10.3168/jds.2008-1957
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water intake and dry matter intake using different lactation curve models

Abstract: The objective was to evaluate 6 different lactation curve models for daily water and dry matter intake. Data originated from the Futterkamp dairy research farm of the Chamber of Agriculture of Schleswig-Holstein in Germany. A data set of about 23,000 observations from 193 Holstein cows was used. Average daily water and dry matter intake were 82.3 and 19.8 kg, respectively. The basic linear mixed model included the fixed effects of parity and test-day within feeding group. Additionally, 6 different functions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
(50 reference statements)
3
14
0
1
Order By: Relevance
“…Most of literature deal with milk yield whereas other conventional dairy traits as fat, protein and somatic cell have received little attention. However there have been examples of modelling of new traits related to milk nutritional quality or health status, as fatty acid composition and water intake (Craninx et al, 2008;Kramer et al, 2009), that are becoming of great importance for breeding and management strategies. Being difficult and expensive to be measured routinely, tools able to describe underlying patterns from few data and with a relevant predictive ability will be presumably required for their modelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of literature deal with milk yield whereas other conventional dairy traits as fat, protein and somatic cell have received little attention. However there have been examples of modelling of new traits related to milk nutritional quality or health status, as fatty acid composition and water intake (Craninx et al, 2008;Kramer et al, 2009), that are becoming of great importance for breeding and management strategies. Being difficult and expensive to be measured routinely, tools able to describe underlying patterns from few data and with a relevant predictive ability will be presumably required for their modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Both models have been successfully used to fit individual curves (Macciotta et al, 2005;Silvestre et al, 2006;Olori et al, 1999) and implemented in the earlier versions of random regression models (Druet et al, 2003;Schaeffer et al, 2000;Schaeffer, 2004). These two functions have been also used for modelling traits other than milk yield as, for example, dry matter and water intake in Holsteins (Kramer et al, 2009) and to estimate gene effect on dairy traits (Strucken et al, 2011). Although they usually outperform the Wood function, especially in different scenarios of data distribution (Silvestre et al, 2006), these two models tend to yield mathematical artifacts such as negative or too high predicted values of milk yield at the beginning or at the end of lactation (Druet et al, 2003;Macciotta et al, 2005;Silvestre et al, 2006).…”
Section: Functionmentioning
confidence: 98%
“…In studies with heifers and lactating dairy cows the ratio of daily water intake to DMI was about 4 L/kg DMI. After weaning cattle ingest food with higher dry matter contents than in milk or MR and have to fulfill their fluid requirements by water intake (Kramer et al, 2009;Lascano and Heinrichs, 2011).…”
Section: Feeding Regimes P Feeding Regimementioning
confidence: 99%
“…Incidentally, further research on this could be interesting to clarify whether the causal relationship would come from both traits. On the basis of their correlation calculation, Lukas et al (2008) and Kramer et al (2009) concluded that daily water consumption can be an indirect trait to predict individual changes in feed intake as well as to identify sick cows.…”
mentioning
confidence: 99%